Effect of Standard No. 2800 Rules for Moment Resisting Frames on the Elastic and Inelastic Behavior of Dual Steel Systems - Veladi, H.; Najafi, H. (Engineering, Technology & Applied Science Research, 2017)
According to most valid Design Codes including the Iranian Seismic Design Code (Standard No. 2800), moment resisting frames in dual systems must have the ability of resisting the 25% of the total lateral load of the dual system independently. This study is conducted to investigate the implementation of this rule for dual steel structures with two types of steel braced frame. Also, its effect on the strength of the structure and the distribution of lateral load between the frames and the bracing system is evaluated. In order to investigate the effect of that rule, structural models with 5, 10 and 15 floors are modeled. Nonlinear static analysis is employed and results are discussed. Following the Standard No. 2008 seems to increase the structure’s lateral resistance and decrease the number of elements entered into the inelastic behavior stage. In general, the structure has a more desirable inelastic behavior.